Security Risk Analysis of QRIS Implementation in Public Locations Using ISO 31000:2018 Framework - M. Fadhli Ma'arif; Melwin Syafrizal; Jeki Kuswanto; Aiko Nur Hendry Yansyah (Journal of Applied Informatics and Computing, 2025)
This study aims to analyze the security risks associated with the implementation of the QRIS (Quick Response Indonesia Standard) payment system in public spaces and provide appropriate mitigation recommendations. The research employs a case study approach with a qualitative research design to explore the perceptions of users and business owners regarding the potential risks involved. Data were collected through semi-structured interviews, risk perception surveys, and document analysis related to QRIS security policies and practices. The findings reveal that the primary risks faced by users and business owners include QR code manipulation, social engineering attacks, unstable internet connections, and low digital literacy. Based on the identified risks, the study suggests several mitigation strategies, including the use of dynamic QRIS, user security education, infrastructure improvements, and the implementation of regular audits. In conclusion, to enhance security and user trust in QRIS, a comprehensive approach is needed, incorporating technical, procedural, and educational aspects in an integrated manner.